The impact of corporate social performance on the cost of debt and access to debt financing for listed European non-financial firms. Issue 4 (August 2018) - La Rosa, Fabio; Liberatore, Giovanni; Mazzi, Francesco; Terzani, Simone
Abstract: This study addresses the controversial issue of how non-financial performance affects the cost of debt capital and access to it. The relationship between corporate social performance and two measures of debt cost (accounting-based and market-based) and the measure of debt access are analysed by means of a multi-theoretical framework combining economics with social theories. By observing a sample of listed European non-financial firms over an 8-year period from 2005 to 2012, we find a negative relationship between corporate social performance and interest rate. Consistent with this result, we find a positive relationship between corporate social performance and debt rating. Thus, corporate social performance has a positive role in reducing the cost of debt capital. Moreover, firms with better corporate social performance are more attractive to lenders in terms of leverage allowance. Overall, our findings provide deeper insight into the reasons why companies should improve their corporate social performance.